THE EFFECT OF BRAIN EXERCISE ON MEMORY OF CHILDREN AGED 7-13 YEARS - Melly Sa'idah; Ria Setia Sari; Febi Ratnasari (Indonesian Journal for Health Sciences, 2023)
The density of children's daily activities causes children stress, as a result children become bored and do not have the opportunity to relax and play, releasing energy and emotional tension experienced. This study aims to determine the effect of brain gym on the memory of children aged 7-13 years at SDN 3 Sukatani, Tangerang Regency.  This study used a quantitative approach.  The research method to be used in this study is Pre-Experiment with One Group Pretest Posttest Design. The statistical analysis test used is the Wilcoxon Signed Rank Test. Sampling was carried out using Total Sampling, researchers used grade V students at SDN 3 Sukatani, which was as many as 100 students. The Wilcoxon Signed Rank Test showed that there was a significant influence between the level of memory before and after brain gym for 4 times a week in 2 weeks, obtained a significant level of p = 0.000 (p = 0.005) thus Ha was accepted. There is an influence of brain gym on the memory of children aged 7-13 years at Public Elementary School 3 Sukatani, Tangerang Regency. It is expected that brain gym movements can increase blood flow and stretch the auto-nerve muscles due to fatigue and excessive learning stress. With regular practice, all brain disorders experienced by children when learning will be resolved